PENGARUH PENGGUNAAN MODUL PEMBELAJARAN MATEMATIKA DENGAN METODE INKUIRI BERBANTUAN WINGEOM UNTUK MENINGKATKAN KEMAMPUAN PENALARAN SPASIAL PESERTA DIDIK - Ardiyanto, Ari (Departemen Matematika, 2025)
This study aims to determine whether the use of Wingeom-assisted learning modules can improve students' spatial reasoning abilities in class IX UPT SMP Negeri 2 Batusangkar. The method used was a quasi-experiment with a non-equivalent posttest-only control group design. The results showed that students who learned using Wingeom-assisted modules had better spatial reasoning abilities than students who used conventional teaching materials, with an average value of 49.31 for the experimental class and 33.26 for the control class. Hypothesis testing using Mann-Whitney showed a P-value of 0.002, which is smaller than 0.05, so ?0 was rejected and ?1 was accepted. Based on the data analysis, a P-value of 0.002 was obtained. Because the value of ? −????? < ? = 0.05 then ?0 is rejected or accept ?1. Thus, it can be concluded that the spatial reasoning ability of students who learn using the mathematics learning module with the Wingeom-assisted inquiry method is better than students who use conventional teaching materials in class IX UPT SMP Negeri 2 Batusangkar in the 2024/2025 academic year. This study concludes that the learning module with the Wingeom-assisted inquiry method is effective in improving students' spatial reasoning abilities.